Pituitary microadenoma associated with hyperprolactinemia and hypercortisolism: a clinical case - Najimova , Aziza; Issayeva , Saodat (Uzbekistan Open Conference, 2026)
Pituitary microadenomas are one of the important neuroendocrine causes of secondary amenorrhea and hyperprolactinemia in women of reproductive age. We present a clinical case of a hormonally active pituitary microadenoma associated with hyperprolactinemia and suspected ACTH-dependent hypercortisolism. A female patient born in 1990 presented with secondary amenorrhea, galactorrhea, weight gain, arterial hypertension, headache, hirsutism, and metabolic disturbances. Hormonal evaluation revealed persistent hyperprolactinemia, elevated ACTH and cortisol levels, and insufficient cortisol suppression during the low-dose dexamethasone suppression test. Magnetic resonance imaging demonstrated progressive enlargement of a pituitary microadenoma during dynamic follow-up. Thyroid ultrasound showed diffuse structural changes of the thyroid gland associated with thyroid dysfunction. Combined therapy with cabergoline, levothyroxine, and metabolic treatment resulted in clinical improvement, reduction of prolactin levels, and restoration of the menstrual cycle. This clinical case highlights the importance of comprehensive endocrine, laboratory, and radiological evaluation in reproductive-aged women presenting with amenorrhea and hyperprolactinemia for early detection of hormonally active pituitary microadenomas and possible Cushing syndrome.
Keywords: pituitary microadenoma; hyperprolactinemia; secondary amenorrhea; hypercortisolism; Cushing syndrome; ACTH; galactorrhea; reproductive dysfunction